Od tkivnega inženirstva do regenerativne medicine - sodoben pristop k rekonstrukciji sečil - Dragin, Urška (Zdravniški vestnik, 2012)
Background: Tissue engineering is a rapidly developing interdisciplinary field, which is becoming an increasingly important part of regenerative medicine. The tissue-engineered substitutes enable the restoration, maintenance and improvement of the functions of damaged or defective tissue. Given the number of urinary tract diseases, which require repair or replacement of the tissue or organ, the techniques of tissue engineering are also gaining importance in regenerative medicine of the urinary tract. Conclusions: A number of animal studies and several clinical studies have shown that it is possible to reconstruct urinary tract tissues and organs using tissue engineering. This review provides a detailed survey of the latestknowledge on the use, effectiveness and limitations of various tissue engineering techniques for reconstruction of the urethra, urinary bladder, ureters and kidneys.
Keywords: matične celice; regenerativna medicina; sečila; tkivne kulture; tkivno inženirstvo